Selection and inspection of power plant elements with application of probability methods; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Krivova L. V. Lyudmila Vladimirovna (Power engineering, 2007)
Заглавие с титульного листа